Diversity and composition of ocular microbiota in contact lens wearers: Efficacy of liposomal ozonated oil - Sánchez-González, María Carmen; Gallardo-Real, Inmaculada; Gutiérrez-Sánchez, Estanislao; De-Hita-Cantalejo, Concepción; Capote-Puente, Raúl; Sánchez-González, José-María (Contact lens & anterior eye, 2025)
To characterize the ocular surface microbiota in regular contact lens wearers with dry eyes and assess the effectiveness of reducing bacterial load using a liposomal ozonated oil solution. This prospective, longitudinal, controlled study randomized subjects into two groups. Group A (45 subjects) received hydroxypropylmethylcellulose (HPMC, Artific®), while Group B (41 subjects) received ozonated sunflower seed oil with soybean phospholipids (OSSO, Ozonest®). Microbial communities were analyzed via DNA metabarcoding of the 16S rRNA gene, and statistical analyses (alpha and beta diversity) were performed in R. Both groups predominantly harbored Staphylococcus caprae, Streptococcus oralis, and Corynebacterium spp., with OSSO and HPMC users showing distinct bacterial profiles. Alpha diversity showed no significant differences, but beta diversity revealed differences in bacterial composition between the groups. The results seem to indicate that the use of ozonized oil reduces the bacterial load compared to the solution used as a control.